Empowerment of the Creative Economy of the Sasirangan Home Industry in Sasirangan Village with the Technology Application of SALAM (Sasirangan WarnA aLAM) - Syahmani Syahmani; Dewi Alfianti; Yogo Dwi Prasetyo; Risma Liyanti; Ibena Waruwu; Muhammad Taufiq; Handi Al Fakhri (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
Craftsmen in Madara Sasirangan lack skills in producing and marketing natural Sasirangan products. To address this, training on natural color Sasirangan technology will be provided in Sasirangan Village, enhancing their production and marketing knowledge and skills. The method used is four stages, namely the 1) Socialization, 2) Training, 3) Monitoring and Evaluation, and 4) Program Continuation stages. Community service was attended by 15 participants/craftsmen for eight meetings from October to November 2025. Lectures and discussions on natural dye extraction techniques, Sasirangan production, and marketing media were held in three meetings. Demonstrations/practices of making natural color Sasirangan from plants were held in three meetings. Furthermore, monitoring and evaluation were held in two meetings. The evaluation results are that (1) There are various types of colors produced from natural dye sources. The suitability between pigment compounds and materials, extraction processes, mordanting, and dyeing can produce good coloring. (2) Participants have an understanding and skills in making Sasirangan natural dyes and marketing them of 80% (good category). Training enhances participants' empowerment in natural Sasirangan product production and marketing, with a focus on natural dye extraction, biomordants for durability, consumer education, and support for sustainable businesses.